Reciprocity System among Muslims in Southern Philippines:The Case of Mèranao Kathatabangan in Times of Natural Disasters - A. MEND0ZA, MYRMA JEAN; ABANTAS-MANALOCON, NORJANNAH; S. MAGOMNANG, ANISALAM; F. QUIRANTE, CATHERINE; AMANODEN, AMANE (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
This paper articulates the concept of kathatabanga reciprocity system of the Mèraneo in the context of natural disasters in Bubong, Lanao del Sur and in Pantao Ragat, Lanao del Norte. These Mèranao populated communities are vulnerable to natural disasters bacause of their geographical location. The purpose of this study is to describe the nature of kathatabanga as a Meranao mutual aid system, its notions and salient dimensions and analyze how social capital influences the observance of kathatabanga. Guided by the social capital theory and social exchange theory, this study utilized data collected from in depth interviews of 15 Mèranao, 8 males and 7 females, aged 25-70 years whose ages range from 25 to 70 years old. Finding of the study show that that in terms of social capital, age,gender, marital status and estimated monthly family income influence kathatabanga. It also depends that the Meranao kathatabanga as a practice carriers with it a moral dimension which is part al Meranao maratabat. It is also a way to strengthen kinship ties and offers an and insurance, Moreover. kathntalanga, as an ag customary pruction in perpetuated and intertwined with the social institutions in the Meranao society